Mann's Introductory statistics - Mann, Prem S. (John Wiley & Sons, 2016)
This revised and expanded edition is designed to motivate and challenge students without a strong mathematics background. Filled with real-world examples, step-by-step explanations, quality exercise sets that link applications to concepts and procedures, and sound pedagogy, this text makes statistics interesting and accessible. New features include problems designed for use with the graphing calculator, directions and screen shots for the Windows version of Minitab throughout the text and an increased focus on technology as a teaching tool.